Utformning av pilot card - Informationsutbyte under lotsning samt dess kvalitet. - Såthén, Beppe; Hammerö, Jeremias (My University, 2017)
A pilot has the task to safely maneuver the ship through a sea area. Since the pilot is an expert in the waters trafficked, they must also be notified specific information regarding the vessel concerned. This information is usually indicated by a pilot card. To answer the question, regarding the design and quality of the pilot card, four professional active pilots have interviewed. Regarding the design of these information sheets the interviews have resulted in highlighting errors and deficiencies identified. The study aims to result in concrete proposals for the design of the pilot card. The authors of this report have the hope that these proposals will be to support of the design of the pilot card in the future.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering